The limits of precision monomer placement in chain growth polymerization - Gody, Guillaume; Zetterlund, Per B.; Perrier, Sébastien; Harrisson, Simon (Nature communications, 2016)
Precise control over the location of monomers in a polymer chain has been described as the ‘Holy Grail’ of polymer synthesis. Controlled chain growth polymerization techniques have brought this goal closer, allowing the preparation of multiblock copolymers with ordered sequences of functional monomers. Such structures have promising applications ranging from medicine to materials engineering. Here we show, however, that the statistical nature of chain growth polymerization places strong limits on the control that can be obtained. We demonstrate that monomer locations are distributed according to surprisingly simple laws related to the Poisson or beta distributions. The degree of control is quantified in terms of the yield of the desired structure and the standard deviation of the appropriate distribution, allowing comparison between different synthetic techniques. This analysis establishes experimental requirements for the design of polymeric chains with controlled sequence of functionalities, which balance precise control of structure with simplicity of synthesis. Chemists increasingly seek to control monomer sequencing in aperiodic copolymers. Here, the authors show that the statistical nature of chain growth strongly limits the achievable control, and establish parameters for polymer design that balance precise control with simplicity of synthesis.